Effect of the combined use of enamel matrix derivative and atelocollagen sponge scaffold on osteoblastic differentiation of mouse induced pluripotent stem cells in vitro. (17th October 2017) - Hisanaga, Y.; Suzuki, E.; Aoki, H.; Sato, M.; Saito, A.; Saito, A.; Azuma, T.
Abstract : Background and Objective: Induced pluripotent stem cells (iPSCs) are a candidate cell source in periodontal regenerative therapy. Enamel matrix derivative (EMD) has been shown to regenerate periodontal tissues, and atelocollagen sponge (ACS) is considered a suitable scaffold or carrier for growth factors. This study aimed to investigate the effect of combined use of EMD and an ACS scaffold on cell behaviors and differentiation of mouse iPSCs (miPSCs) in vitro. Material and Methods: Following embryonic body formation from miPSCs, dissociated cells (miPS‐EB‐derived cells) were seeded onto ACS with or without EMD, and cultured in osteoblast differentiation medium. Scanning electron microscopy and histological analyses were used to assess cell morphology and infiltration within the ACS. Cell viability (metabolism) was determined using an MTS assay, and expression of mRNA of osteoblastic differentiation markers was assessed by quantitative RT ‐PCR. Alkaline phosphatase (ALP) staining intensity and activity were evaluated. Mineralization was assessed by von Kossa staining, and calcium content was quantitated using the methylxylenol blue method. Results: By 24 hours after seeding, miPS‐EB‐derived cells in both the EMD and control groups had attached to and infiltrated the ACS scaffold. Scanning electron microscopy images revealed that by day 14, many cytoplasmic protrusions and extracellular deposits, suggestive of calcified matrix, were present in the EMD group. There was a time‐dependent increase in cell viability up to day 3, but no difference between groups was observed at any time point. The levels expressed of ALP and osterix genes were significantly higher in the EMD group than in the control group. Expression of runt‐related transcription factor 2 was increased in the EMD group compared with the control group on day 7. EMD upregulated the expression of bone sialoprotein and osteopontin on day 14, whereas expression of osteocalcin was lower at all time points. The staining intensity and activity of ALP were higher in the EMD group than in the control group. Mineralization levels and calcium contents were significantly higher in the EMD group throughout the observation period. Conclusion: These data suggest that combining ACS with EMD increases levels of osteoblastic differentiation and mineralization in miPS‐EB‐derived cells, compared with ACS used alone.